Analisis Performa Indeks Stabilitas Termodinamik Radiosonde dalam Memprediksi Kejadian Thunderstorm di Bandar Udara Juanda: Indonesia - Rafi, Rayhan; Athallah, Yusron Faiz; Haryanto, Yosafat Donni (Jurnal Sains & Teknologi Lingkungan, 2026)
Operational flight safety at Juanda International Airport relies heavily on the accuracy of short-term weather predictions (nowcasting), particularly in anticipating significant convective weather phenomena. This study aims to evaluate the performance of six thermodynamic instability indices (CAPE, K-Index, Lifted Index, Total-Totals, Showalter Index, and SWEAT) derived from 00.00 UTC radiosonde data in predicting Thunderstorm events occurring between 00.00–06.00 UTC. Using observational data from September 2024 to August 2025, verification was conducted through visual distribution analysis (Box Plot) and statistical contingency table scores (POD, FAR, CSI). Seasonal analysis shows that instability indices exhibit higher sensitivity during the Rainy Season (DJF) compared to the Dry Season (JJA), consistent with the greater frequency of convective events in that period. Quantitatively, the Lifted Index (LI) demonstrates relatively superior validation performance, indicated by the highest Critical Success Index (CSI) among all indices. This suggests that stability parameters based on parcel temperature differences are more representative of local atmospheric conditions than purely energy-based parameters such as CAPE. However, the generally low CSI values (< 0.2) indicate that these indices still have limited sensitivity in capturing local atmospheric dynamics at Juanda, as reflected by the relatively high occurrences of Misses and False Alarms. This study recommends prioritizing the use of LI, while further investigation on local threshold adjustments and extending the temporal scale of analysis is necessary to improve predictive performance.